Desenvolvimento do game educativo “Reinos da luz” sobre óptica-cores na estratégia de ensino de física - Barbosa, Valdenilson Santos (2020)
The teaching of physics in Brazilian schools has presented many problems, since it has been focused on teaching entrance exam contents with many reproductions of formulas, often applying traditional methodologies, whose teachers, holders of knowledge, aim to expose subjects for resolution of problems. In addition, physics has been presented far from students' daily lives, relating its concepts to complex applications that are difficult to understand. In the expectation of bringing the scientific world closer to the students, and in the search for an innovative methodology that provides an engagement linked to the interest of learning physics, we propose to use Gamification, through the mechanics of games, as a methodological strategy to promote learning and interaction among students. Thus, the objective of our Educational Product is to build a game for cell phones in order to promote the learning of concepts of Optics-Colors, using the dynamics of Gamification for students of the 2nd year of High School.